Ectopic pregnancy, study at Victor Lazarte Echegaray Hospital - Romero, Karin (2015)
OBJECTIVE: To determine the relationship of some epidemiological, clinical, diagnostic and therapeutic factors in ectopic pregnancy. DESIGN: Retrospective. LOCATION: Department of Gynecology of the Hospital Victor Lazarte Echegaray - EsSalud of Trujillo. MATERIALS AND METHODS: Fifty-one patients who had operative diagnosis of ectopic pregnancy in the period May 1995 to April 2000. RESULTS: Ectopic pregnancy had a frequency of 1 in every 133 births; 33.3% of patients were between 36 and 45 years old. The predisposing factors were pelvic inflammatory disease, infertility and uterine surgical curettage; the most widely used diagnostic method was ultrasound (66.7%); The most frequent location was tubal (90.2%); major complications were anemia (68.6%) and hypovolemic shock (13.7%). CONCLUSION: ectopic pregnancy related characteristics were similar to those described in the literature.